Process for the purification of carbon dioxide-based polyether polyols and products thereof

CN122940995APending Publication Date: 2026-10-20CHINA TIANCHEN ENGINEERING CORPORATION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611021779.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

尽管如此,双金属氰化物催化剂的使用仍会导致聚醚多元醇中存在锌、钴等过渡金属元素,影响聚醚多元醇的色度和纯度,需要进一步去除

Benefits of technology

(1)本发明所述方法采用第一溶剂、第二溶剂和吸附剂,对二氧化碳基聚醚多元醇进行杂质的沉降和吸附,然后利用分相和过滤除去杂质,在此基础上除去溶剂,即可得到精制的二氧化碳基聚醚多元醇产品;未使用酸或碱试剂进行中和,避免了大量废盐废水的产生,且对装置的要求不高,溶剂回收简单,工艺流程十分安全,生产成本较低,展现出了较高的工业应用价值;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a purification method for carbon dioxide-based polyether polyols and the product thereof. The method includes the following steps: (1) mixing crude carbon dioxide-based polyether polyol with a first solvent, a second solvent, and an adsorbent to obtain a mixture; (2) separating the mixture in step (1) to obtain an upper layer; (3) filtering and desolventizing the upper layer to obtain the carbon dioxide-based polyether polyol product; the first solvent is selected from C1-C4 alcohols, and the second solvent is selected from halogenated hydrocarbons; the crude carbon dioxide-based polyether polyol contains transition metal impurities; the process flow of the above method of this invention is simple, does not require the participation of acid or alkali, and can effectively remove the bimetallic cyanide catalyst in the carbon dioxide-based polyether polyol and optimize the molecular weight distribution of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic synthesis, and particularly relates to a method for purifying carbon dioxide-based polyether polyols and their products. Background Technology

[0002] Carbon dioxide-based polyether polyols, also known as polyether carbonate polyols, are copolymers of propylene oxide and carbon dioxide with hydroxyl-terminated ends, containing both carbonate and ether bonds in their molecular chains. Their preparation mainly involves two methods: ring-opening polymerization of cyclic carbonates and controlled copolymerization of carbon dioxide and epoxy compounds. The former, due to its low reaction efficiency and weak control over carbonate units, is currently mostly used in laboratory research; while the latter has been widely applied. By adding chain transfer agents during the ring-opening copolymerization of epoxy compounds such as propylene oxide and carbon dioxide, and controlling the chain transfer of the reaction, hydroxyl-terminated polycarbonates containing both polyether and polycarbonate units are obtained. Carbon dioxide polyethers not only possess the properties of polycarbonates but also the advantages of polyether polyols, such as low-temperature flexibility. Polyurethane materials prepared from them exhibit excellent antioxidant, abrasion-resistant, and chemical-resistant properties, and compared to polyester-type polyols, they also have good hydrolytic stability, making them a green and environmentally friendly product.

[0003] Currently, the synthesis of polyether polyols typically uses alkali metals, alkaline earth metals, or their hydroxides as catalysts. This method easily introduces alkaline metal ions into the polyether polyols, leading to violent prepolymerization reactions during polyurethane production. This results in the polyurethane product becoming unusable due to agglomeration, thus requiring their removal. The current purification method for polyether polyols mainly involves neutralization-filtration, which often requires the use of organic and inorganic acids, increasing the complexity of the production process and raising production costs.

[0004] Bimetallic cyanide (DMC) catalysts are heterogeneous catalysts with advantages such as simple preparation, relatively low cost, and insensitivity to water and oxygen. Compared with alkaline earth metal catalysts, this type of catalyst does not introduce excessive alkaline earth metal elements. Nevertheless, the use of bimetallic cyanide catalysts still results in the presence of transition metal elements such as zinc and cobalt in polyether polyols, affecting the color and purity of the polyether polyols, requiring further removal.

[0005] Therefore, it is still of great significance to develop a purification method for carbon dioxide-based polyether polyols that can effectively remove bimetallic cyanide catalysts from them and optimize the molecular weight distribution of the products. Summary of the Invention

[0006] The purpose of this invention is to provide a purification method for carbon dioxide-based polyether polyols and the product thereof. The method includes the following steps: (1) mixing crude carbon dioxide-based polyether polyol with a first solvent, a second solvent, and an adsorbent to obtain a mixture; (2) separating the mixture in step (1) to obtain an upper layer; (3) filtering and desolventizing the upper layer in step (2) to obtain a carbon dioxide-based polyether polyol product; the first solvent is selected from C1-C4 alcohols, and the second solvent is selected from halogenated hydrocarbons; the crude carbon dioxide-based polyether polyol contains transition metal impurities; the process flow of the above method of this invention is simple, does not require the participation of acid or alkali, and can effectively remove the bimetallic cyanide catalyst in the carbon dioxide-based polyether polyol and optimize the molecular weight distribution of the product.

[0007] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for purifying carbon dioxide-based polyether polyols, the method comprising the following steps: (1) The crude carbon dioxide-based polyether polyol is mixed with the first solvent, the second solvent, and the adsorbent to obtain a mixture; (2) Separate the mixture from step (1) to obtain the upper layer; (3) The upper liquid in step (2) is filtered and desolventized to obtain carbon dioxide-based polyether polyol product; The first solvent is selected from C1-C4 alcohols, and the second solvent is selected from halogenated hydrocarbons; the crude carbon dioxide-based polyether polyol contains transition metal impurities.

[0008] In the method described in this invention, the purpose of adding the first solvent is to utilize the limited solubility of carbon dioxide-based polyether polyols in low-carbon alcohols such as ethanol, thereby promoting the emulsification of the carbon dioxide-based polyether polyols, releasing the bimetallic cyanide catalyst, and achieving effective adsorption and sedimentation of the catalyst by the adsorbent, ultimately removing it from the polyether polyol. Although emulsification is beneficial for catalyst removal, excessive emulsification will cause the polyether polyol to adhere to the filter wall during subsequent filtration, resulting in excessive loss of polyether polyol. Therefore, a second solvent is needed to improve the dispersibility of the polyether polyol and impurities in the solution, on the one hand to avoid excessive emulsification, and on the other hand to facilitate sufficient contact between impurities and the adsorbent, thereby improving adsorption efficiency.

[0009] In the method of the present invention, in step (2), phase separation is performed to obtain an upper clear liquid and a bottom viscous impurity; wherein, the upper clear liquid is an organic solution containing carbon dioxide-based polyether polyol, and the bottom precipitate is a mixture of catalyst and adsorbent containing transition metal elements; then in step (3), pressure filtration is applied to remove excessively high molecular weight carbon dioxide-based polyether polyol segments, the filtered solution is collected, and then the solvent is removed to obtain a carbon dioxide-based polyether polyol product with high purity and relatively uniform molecular weight distribution.

[0010] Preferably, the first solvent is selected from methanol, ethanol, isopropanol, n-propanol or n-butanol.

[0011] Preferably, the second solvent is selected from dichloromethane, chloroform, or bromoethane.

[0012] Preferably, the adsorbent is selected from solid acid adsorbents.

[0013] Preferably, the solid acid adsorbent is selected from silicates; the silicates include magnesium aluminum silicates; for example, the adsorbent is selected from magnesium aluminum silicates or a mixture of magnesium aluminum silicates and other silicates.

[0014] Preferably, the solid acid adsorbent is selected from kaolin.

[0015] Preferably, the particle size of the adsorbent is selected from 40~250μm, such as 50μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm or 220μm; preferably, the specific surface area is ≥80m². 2 / g, for example 90m 2 / g, 100 m 2 / g or 120 m 2 / g etc.

[0016] Preferably, in step (1), the mass ratio of the crude carbon dioxide-based polyether polyol to the first solvent is 100:(0.5~80), for example, 100:1, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, 100:50, 100:55, 100:60, 100:65, 100:70 or 100:75, etc., preferably 100:(25~60), and more preferably 100:(45~55).

[0017] Preferably, in step (1), the mass ratio of the crude carbon dioxide-based polyether polyol to the second solvent is 100:(0.5~80), for example, 100:1, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, 100:50, 100:55, 100:60, 100:65, 100:70 or 100:75, etc., preferably 100:(25~60), and more preferably 100:(45~55).

[0018] Preferably, in step (1), the mass ratio of the crude carbon dioxide-based polyether polyol to the adsorbent is 100:(0.01~10), for example, 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5, 100:6, 100:6.5, 100:7, 100:7.5, 100:8, 100:8.5, 100:9 or 100:9.5, etc., preferably 100:(0.1~5), and more preferably 100:(0.5~1.5).

[0019] Preferably, the mass ratio of the first solvent and the second solvent in step (1) is 1:(0.8~1.25), for example 1:0.9, 1:1 or 1:1.1, etc.

[0020] Preferably, the mixing method in step (1) includes adding a first solvent, a second solvent, and an adsorbent to the crude carbon dioxide-based polyether polyol and stirring.

[0021] Preferably, the stirring temperature is 15~50℃, such as 20℃, 25℃, 30℃, 35℃, 40℃ or 45℃.

[0022] Preferably, the stirring time is 0.5 to 10 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, or 9 hours.

[0023] Preferably, the phase separation method in step (2) includes centrifuging the mixture in step (1).

[0024] Preferably, the centrifugation speed is 1000~5000 rpm; for example, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm or 4500 rpm, etc.

[0025] Preferably, the centrifugation time is 10-50 minutes, such as 20 minutes, 30 minutes, or 40 minutes.

[0026] Preferably, the filtration in step (3) is performed using pressure filtration.

[0027] Preferably, the filtration in step (3) is carried out in a filtration system, which includes a stainless steel cavity, a filter membrane and an air source; the air source is used for pressurized filtration.

[0028] Preferably, the pore size of the filter membrane is selected from 0.1~5μm, such as 0.5μm, 1μm, 2μm, 3μm or 4μm.

[0029] Preferably, the filtered air pressure is 0.5~6MPa; for example, 1MPa, 2MPa, 3MPa, 4MPa or 5MPa.

[0030] Preferably, the filter membrane material is selected from one or more of polytetrafluoroethylene, polypropylene, or nylon.

[0031] Preferably, the desolventizing method in step (3) is selected from rotary evaporation.

[0032] Preferably, the temperature of the rotary evaporation is selected from 30~90℃, such as 35℃, 45℃, 55℃, 65℃, 75℃ or 85℃, etc.; preferably 40~80℃.

[0033] Preferably, the transition metal impurities include metal ions such as zinc, cobalt, and sodium; Preferably, the transition metal impurity originates from the bimetallic cyanide catalyst used in the preparation of crude carbon dioxide-based polyether polyol.

[0034] In a second aspect, the present invention provides carbon dioxide-based polyether polyol products obtained by the method described in the first aspect.

[0035] Preferably, the content of transition metal elements in the carbon dioxide-based polyether polyol product is ≤15ppm.

[0036] Preferably, the molecular weight distribution index (PDI) of the carbon dioxide-based polyether polyol product is 1.1 to 2, more preferably 1.3 to 1.5.

[0037] Thirdly, the present invention provides a method for preparing carbon dioxide-based polyether polyols, the method comprising using a bimetallic cyanide as a catalyst to prepare a crude carbon dioxide-based polyether polyol, and then using the method described in the first aspect to prepare the carbon dioxide-based polyether polyol.

[0038] Compared with the prior art, the present invention has the following beneficial effects: (1) The method of the present invention uses a first solvent, a second solvent and an adsorbent to precipitate and adsorb impurities in carbon dioxide-based polyether polyol, and then removes impurities by phase separation and filtration. Based on this, the solvent is removed to obtain a refined carbon dioxide-based polyether polyol product. No acid or alkali reagents are used for neutralization, which avoids the generation of a large amount of waste salt and wastewater. The requirements for the equipment are not high, the solvent recovery is simple, the process is very safe, the production cost is low, and it shows high industrial application value. (2) The purification method used in this invention can optimize the molecular weight distribution on the one hand, and effectively remove the bimetallic cyanide catalyst on the other hand, thus significantly reducing the content of transition metal elements in the product. Attached Figure Description

[0039] Figure 1 This is a gel permeation chromatogram of the raw materials in a specific embodiment of the present invention; Figure 2 This is the gel permeation chromatogram of the product in Example 1 of the present invention; Figure 3 This is the gel permeation chromatogram of the product in Example 2 of the present invention; Figure 4 This is the gel permeation chromatogram of the product in Example 3 of the present invention; Figure 5 This is the gel permeation chromatogram of the product in Example 4 of the present invention; Figure 6 This is the gel permeation chromatogram of the product in Example 5 of the present invention; Figure 7 This is the gel permeation chromatogram of the product in Example 6 of the present invention; Figure 8 This is the gel permeation chromatogram of the product in Comparative Example 1 of this invention; Figure 9 This is the gel permeation chromatogram of the product in Comparative Example 2 of this invention; Figure 10 This is the gel permeation chromatogram of the product in Comparative Example 3 of this invention. Detailed Implementation

[0040] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0041] In the following examples and comparative examples, the adsorbent was selected from kaolin with a particle size of 200 mesh and a specific surface area of ​​600 m². 2 / g; The crude carbon dioxide-based polyether polyol (raw material) to be purified was prepared using a bimetallic cyanide as a catalyst. Its metal element content is shown in Table 1, and its molecular weight distribution is shown in Tables 2 and 3. Figure 1 As shown.

[0042] The characterization test methods are as follows: The metal element content was measured using an ICP instrument, and the molecular weight distribution of carbon dioxide polyether polyols was tested using liquid gel chromatography. Example 1

[0043] 100g of the crude carbon dioxide-based polyether polyol to be purified was added to a 500mL single-necked flask, along with 50g of dichloromethane, 50g of ethanol, and 1g of kaolin adsorbent. The mixture was stirred at room temperature for 30min, followed by centrifugation at 3000rpm for 30min. The supernatant was then separated and subjected to positive pressure filtration with a 1μm filter membrane and an air inlet pressure of 3MPa. After filtration, the purified carbon dioxide-based polyether polyol product was obtained. The content of different metal elements was measured, as shown in Table 1. Simultaneously, its molecular weight distribution was also measured. Figure 2 As shown in Table 2, further analysis yields molecular weight distribution values. Example 2

[0044] The only difference between this embodiment and Example 1 is that the amount of dichloromethane added is changed from 50g to 25g, while the other parameters and conditions are the same as in Example 1.

[0045] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 3 As shown in Table 2, further analysis yields molecular weight distribution values. Example 3

[0046] The only difference between this embodiment and Embodiment 1 is that the amount of ethanol added is changed from 50g to 25g; other parameters and conditions are the same as in Embodiment 1.

[0047] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 4 As shown in Table 2, further analysis yields molecular weight distribution values. Example 4

[0048] The only difference between this embodiment and Embodiment 1 is that the amount of kaolin adsorbent added is changed from 1g to 0.5g, while the other parameters and conditions are the same as in Embodiment 1.

[0049] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 5 As shown in Table 2, further analysis yields molecular weight distribution values. Example 5

[0050] The only difference between this embodiment and Embodiment 1 is that the amount of kaolin adsorbent added is changed from 1g to 3g, while the other parameters and conditions are the same as in Embodiment 1.

[0051] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 6 As shown in Table 2, further analysis yields molecular weight distribution values. Example 6

[0052] The only difference between this embodiment and Example 1 is that ethanol is replaced with n-butanol and dichloromethane is replaced with bromoethane. All other parameters and conditions are the same as in Example 1.

[0053] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 7 As shown in Table 2, further analysis yields molecular weight distribution values.

[0054] Comparative Example 1 The only difference between this comparative example and Example 1 is that dichloromethane is not added; all other parameters and conditions are the same as in Example 1.

[0055] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 8 As shown in Table 2, further analysis yields molecular weight distribution values.

[0056] Comparative Example 2 The only difference between this comparative example and Example 1 is that ethanol is not added; all other parameters and conditions are the same as in Example 1.

[0057] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 9 As shown in Table 2, further analysis yields molecular weight distribution values.

[0058] Comparative Example 3 The only difference between this comparative example and Example 1 is that no clay adsorbent is added; all other parameters and conditions are the same as in Example 1.

[0059] The contents of different types of metal elements in the obtained product are shown in Table 1. Their molecular weight distribution was also measured. Figure 10 As shown in Table 2, further analysis yields molecular weight distribution values.

[0060] Table 1 Crude polyether polyols 59.180 125.380 none Example 1 0.287 0.566 none Example 2 0.476 0.722 none Example 3 1.092 2.125 none Example 4 0.826 1.523 none Example 5 0.481 0.736 47.286 Example 6 0.302 0.598 none Comparative Example 1 6.777 15.055 none Comparative Example 2 7.949 21.735 none Comparative Example 3 47.734 107.813 none As can be seen from the data in Table 1, the content of transition metal ions in the carbon dioxide-based polyether polyol product obtained by the method described in this invention is significantly lower than that in the crude raw material product, and the content of transition metal elements can reach below 15 ppm.

[0061] Comparing Example 1, Comparative Example 1, and Comparative Example 2, it is evident that dichloromethane and ethanol must be used synergistically to achieve the optimal demetallization effect. Without the addition of dichloromethane or ethanol, the residual amounts of Co and Zn elements significantly increased, far exceeding the 0.2-0.5 ppm level of Example 1.

[0062] Comparing Examples 1 and 6, it can be seen that replacing ethanol with n-butanol by mass and replacing dichloromethane with bromoethane by mass resulted in lower residual amounts of Co and Zn elements. This indicates that other solvent combinations of the same type can also achieve the same demetallization effect as ethanol and dichloromethane.

[0063] Comparing Example 1 and Comparative Example 3, it can be seen that the bleaching clay adsorbent also plays an important role in removing metal ions such as Zn and Co. Without bleaching clay, the residual levels of Co and Zn are relatively high (Co: 47.734 ppm, Zn: 107.813 ppm). However, comparing Examples 1, 4, and 5 (bleaching clay dosages of 1 g, 0.5 g, and 3 g, respectively), it is clear that the amount of bleaching clay used needs to be appropriate. When the dosage is too low, the removal effect on impurities such as Zn and Co is poor; while when the dosage is too high, alkali metal elements such as Na are introduced; this may be due to the Na element introduced by the excessive bleaching clay itself.

[0064] Table 2 Crude polyether polyols 1.892 Example 1 1.392 Example 2 1.453 Example 3 1.699 Example 4 1.458 Example 5 1.405 Example 6 1.414 Comparative Example 1 1.505 Comparative Example 2 1.804 Comparative Example 3 1.665 As can be seen from Table 2, the molecular weight distribution of the carbon dioxide-based polyether polyol products obtained in the embodiments of the present invention is more uniform; specifically: Compared with Example 1 and Comparative Example 3, even with the use of a mixed solvent, the PDI remained high (1.665) in the absence of bleaching clay. This indicates that solvent dissolution and filtration alone cannot effectively control the molecular weight distribution. Furthermore, combining Examples 1, 4, and 5, it can be seen that the PDI initially decreases and then slightly increases with increasing bleaching clay dosage, suggesting that the amount of bleaching clay used should be within a reasonable range and should not be too much or too little.

[0065] Comparing Example 1, Example 3 and Comparative Example 2, it can be seen that ethanol can effectively control the molecular weight distribution of polyether polyols.

[0066] Comparing Examples 1 and 6, it can be seen that replacing ethanol by mass with n-butanol and dichloromethane by mass with bromoethane resulted in a PDI of 1.414, which is close to that of Example 1 (1.392). This indicates that other solvent combinations of the same type can also effectively control the molecular weight distribution of carbon dioxide-based polyether polyols.

[0067] Comparing Examples 1 and 2 with Comparative Example 1, it is evident that the absence of dichloromethane leads to an increase in PDI. This may be because, although ethanol is a polar solvent, its solubility for the polyether polyol bulk (especially the medium- and high molecular weight fractions) is limited. Without dichloromethane, the system may become too viscous or dissolve unevenly, and some high molecular weight segments may also agglomerate abnormally, ultimately resulting in a wider molecular weight distribution in the filtered product.

[0068] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for purifying carbon dioxide-based polyether polyols, characterized in that, The method includes the following steps: (1) The crude carbon dioxide-based polyether polyol is mixed with the first solvent, the second solvent, and the adsorbent to obtain a mixture; (2) Separate the mixture from step (1) to obtain the upper layer; (3) The upper liquid in step (2) is filtered and desolventized to obtain carbon dioxide-based polyether polyol product; The first solvent is selected from C1-C4 alcohols, and the second solvent is selected from halogenated hydrocarbons; the crude carbon dioxide-based polyether polyol contains transition metal impurities.

2. The method according to claim 1, characterized in that, The first solvent is selected from one of methanol, ethanol, isopropanol, n-propanol, or n-butanol; Preferably, the second solvent is selected from one or more of dichloromethane, chloroform, or bromoethane; Preferably, the adsorbent is selected from solid acid adsorbents; Preferably, the solid acid adsorbent is selected from silicates; the silicates include magnesium aluminum silicates; Preferably, the solid acid adsorbent is selected from kaolin; Preferably, the particle size of the adsorbent is selected from 40~250μm, and more preferably, the specific surface area is ≥80m². 2 / g.

3. The method according to claim 1, characterized in that, In step (1), the mass ratio of the crude carbon dioxide-based polyether polyol to the first solvent is 100:(0.5~80), preferably 100:(25~60), and more preferably 100:(45~55); Preferably, in step (1), the mass ratio of the crude carbon dioxide-based polyether polyol to the second solvent is 100:(0.5~80), more preferably 100:(25~60), and even more preferably 100:(45~55); Preferably, in step (1), the mass ratio of the crude carbon dioxide-based polyether polyol to the adsorbent is 100:(0.01~10), more preferably 100:(0.1~5), and even more preferably 100:(0.5~1.5); Preferably, the mass ratio of the first solvent and the second solvent in step (1) is 1:(0.8~1.25).

4. The method according to claim 1, characterized in that, The mixing method in step (1) includes adding a first solvent, a second solvent, and an adsorbent to the crude carbon dioxide-based polyether polyol and stirring. Preferably, the stirring temperature is 15~50℃; Preferably, the stirring time is 0.5 to 10 hours.

5. The method according to claim 1, characterized in that, The phase separation method in step (2) includes centrifuging the mixture from step (1); Preferably, the centrifugation speed is 1000~5000 rpm; Preferably, the centrifugation time is 10-50 minutes.

6. The method according to claim 1, characterized in that, In step (3), pressure filtration is used for the filtration process; Preferably, the pore size of the filter membrane is selected from 0.1~5μm; Preferably, the filtered air pressure is 0.5~6MPa; Preferably, the filter membrane material is selected from one or more of polytetrafluoroethylene, polypropylene, or nylon.

7. The method according to claim 1, characterized in that, The solvent removal method in step (3) is selected from rotary evaporation; Preferably, the temperature of the rotary evaporation is selected from 30~90℃, more preferably 40~80℃.

8. The method according to claim 1, characterized in that, The transition metal impurities include zinc, cobalt, or sodium; Preferably, the transition metal impurity originates from the bimetallic cyanide catalyst used in the preparation of crude carbon dioxide-based polyether polyol.

9. The carbon dioxide-based polyether polyol product obtained by the method according to any one of claims 1-8; Preferably, the content of transition metal elements in the carbon dioxide-based polyether polyol product is ≤15ppm; Preferably, the molecular weight distribution index (PDI) of the carbon dioxide-based polyether polyol product is selected from 1.1 to 2, and more preferably from 1.3 to 1.

5.

10. A method for preparing a carbon dioxide-based polyether polyol, characterized in that, The method includes preparing a crude carbon dioxide-based polyether polyol using a bimetallic cyanide as a catalyst, and then preparing the carbon dioxide-based polyether polyol using the method described in any one of claims 1-9.